Biomarkers in acute graft-versus-host disease: new insights. (December 2019) - Srinagesh, Hrishikesh K.; Levine, John E.; Ferrara, James L.M.
Hematopoietic cell transplantation (HCT) is a potentially curative therapy for hematologic malignancies that relies on the graft- versus -leukemia (GVL) effect to eradicate malignant cells. GVL is tightly linked to graft- versus -host disease (GVHD) however, in which donor T cells damage healthy host tissues. Acute GVHD occurs in nearly 50% of patients receiving HCT, and damages the skin, liver, and gastrointestinal (GI) tract. The organ stages are totaled in an overall grade (I–IV), and severe (grade III/IV) GVHD has a high mortality rate (50–70%). In the past decade, serum biomarkers have emerged as an additional potential measurement of acute GVHD severity. The discovery and validation of GVHD biomarkers is a principal objective of the Mount Sinai Acute GVHD International Consortium (MAGIC), a group of 25 HCT centers conducting GVHD research. MAGIC has validated an algorithm that combines two GI biomarkers (ST2 and REG3α) into a single value that estimates the probability of 6 month nonrelapse mortality (NRM) for individual patients, known as the MAGIC algorithm probability (MAP). The MAP reflects GI crypt damage and serves as a 'liquid biopsy' of the lower GI tract; it also predicts response to treatment and maximum GVHD severity and is now commercially available and widely used among scores of centers in clinical practice. The MAP is the focus of this review, with consideration of the categorization of types of biomarkers as defined by the United States National Institutes of Health (NIH) and Food and Drug Administration (FDA).